Penerapan Asas Iktikad Baik Pada Kontrak Elektronik Jasa Titip Tiket Konser di Media Sosial - Rajavi, Zeta Kirana; Parmitasari, Indah (Fakultas Hukum Universitas Islam Indonesia, 2025)
The principle of good faith is an important basis for implementing a contract. This principle aims to provide legal certainty for the parties so that contracts can be carried out fairly and without harming either party. This also applies to concert ticket services on social media. This research aims to examine how the principle of good faith is applied in electronic contracts for concert ticket deposit services on social media? and the legal consequences of not implementing the principle of good faith? This research uses a normative juridical research type, with a conceptual approach, statutory regulations and cases. Data was obtained through library research on primary legal materials, secondary legal materials and tertiary legal materials using descriptive-qualitative analysis methods. The results of this research conclude that the application of the principle of good faith has not been fully implemented in electronic contracts for concert ticket deposit services on social media, both in terms of subjective and objective principles of good faith. Failure to implement the principle of good faith results in defects of will in the agreement made and leads to breach of contract, namely failure to fulfill achievements in the form of concert tickets which are the object of the contract.